2021
DOI: 10.21203/rs.3.rs-838905/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphism Analysis and Expression Profile of the Estrogen Receptor 2 Gene in Leizhou Black Duck

Abstract: BackgroundOur previous study on the ovarian transcriptomic analysis in Leizhou black duck revealed that the ESR2 gene was involved in hormone regulation in reproduction and the estrogen signaling pathway related to reproductive performance was enriched. This suggested that ESR2 may have a functional role in the reproductive performance of the Leizhou black duck. Thus, this study aimed at evaluating the polymorphism of the ESR2 gene and its association with egg-laying traits and the distribution pattern of ESR2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Research on the identification of poultry genes and their association with economic traits is increasing, which has contributed to identifying new genetic markers to more accurately select animals to improve poultry growth performance ( Bhattacharya et al, 2019 ; Asiamah et al, 2022 ). Gao et al (2020) reported that 46 SNPs were detected in the GnRH gene of 2 Sichuan White goose populations.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Research on the identification of poultry genes and their association with economic traits is increasing, which has contributed to identifying new genetic markers to more accurately select animals to improve poultry growth performance ( Bhattacharya et al, 2019 ; Asiamah et al, 2022 ). Gao et al (2020) reported that 46 SNPs were detected in the GnRH gene of 2 Sichuan White goose populations.…”
Section: Results and Disscusionmentioning
confidence: 99%